Pharmacy Students’ Ability to Think About Thinking - Schneider, Eric F. (Am J Pharm Educ, 2014)
Objective. To investigate students’ metacognitive skills to distinguish what they know from what they do not know, to assess students’ prediction of performance on a summative examination, and to compare student-identified incorrect questions with actual examination performance in order to improve exam quality. Methods. Students completed a test-taking questionnaire identifying items perceived to be incorrect and rating their test-taking ability. Results. Higher performing students evidenced better metacognitive skills by more accurately identifying incorrect items on the exam. Most students (86%) underpredicted their performance on the summative examination (actual=73.6 ± 7.1 versus predicted=63.7 ± 10.5, p<0.05). Student responses helped refine items and resulted in examination changes. Conclusion. Metacognition is important to the development of life-long learning in pharmacy students. Students able to monitor what they know and what they do not know can improve their performance.